Blur-resistant Perimetric Stimuli - Horner, Douglas G. (2013)
PURPOSE: To develop perimetric stimuli which are resistant to the effects of peripheral defocus. METHODS: One eye each was tested on subjects free of eye disease. Experiment 1 assessed spatial frequency, testing 12 subjects at eccentricities from 2° to 7°, using blur levels from 0 D to 3 D for two (Gabor) stimuli (spatial standard deviation (SD) = 0.5°, spatial frequencies of 0.5 and 1.0 cpd). Experiment 2 assessed stimulus size, testing 12 subjects at eccentricities from 4° to 7°, using blur levels 0 D to 6 D, for two Gaussians with SDs of 0.5° and 0.25° and a 0.5 cpd Gabor with SD of 0.5°. Experiment 3 tested 13 subjects at eccentricities from fixation to 27°, using blur levels 0 D to 6 D, for Gabor stimuli at 56 locations; the spatial frequency ranged from 0.14 to 0.50 cpd with location, and SD was scaled accordingly. RESULTS: In experiment 1, blur by 3 D caused a small decline in log contrast sensitivity (CS) for the 0.5 cpd stimulus (mean ± SE = −0.09 ± 0.08 log unit) and a larger (t = 7.7, p <0.0001) decline for the 1.0 cpd stimulus (0.37 ± 0.13 log unit). In experiment 2, blur by 6 D caused minimal decline for the larger Gaussian, by −0.17 ± 0.16 log unit, and larger (t >4.5, p < 0.001) declines for the smaller Gaussian (−0.33 ± 0.16 log unit) and the Gabor (−0.36 ± 0.18 log unit). In experiment 3, blur by 6 D caused declines by 0.27 ± 0.05 log unit for eccentricities from 0° to 10°, by 0.20 ± 0.04 log unit for eccentricities from 10° to 20° and 0.13 ± 0.03 log unit for eccentricities from 20°–27°. CONCLUSIONS: Experiments 1 & 2 allowed us to design stimuli for Experiment 3 that were resistant to effects of peripheral defocus.